(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The purpose of this paper is to examine how higher education in India is currently supported, as well as the viability as well as feasibility of alternative financing plans. In India, the government pays for the majority of higher education. Furthermore, since higher education helps both individuals and communities, and since it draws society’s wealthier members, a case might be made for moving the economic strain from the social to the private realm. Given financial constraints and concerns about justice, it is suggested that paying higher education largely via general tax revenue may not be the best long-term plan. As a consequence, many policy solutions are considered, including public support of higher education, student loans, graduate tax, student fees, and private sector engagement. A discriminating pricing system, it is said, would be the most efficient and equitable of the possibilities. While the government will continue to fund a large portion of higher education costs owing to socioeconomic and political realities, efforts should be made to build a funding model that integrates a range of techniques rather than relying on a single one. Fee and subsidy policies should also be differentiated across several levels as well as varieties of higher education, according to the authors.